Effects of the Good Behavior Game on the Behavioral, Emotional, and Social Problems of Children With Psychiatric Disorders in Special Education Settings. (July 2016) - Breeman, Linda D.; van Lier, Pol A. C.; Wubbels, Theo; Verhulst, Frank C.; van der Ende, Jan; Maras, Athanasios; Struiksma, A. J. Chris; Hopman, Juliette A. B.; Tick, Nouchka T.
Teaching children with psychiatric disorders can be a challenging task. The purpose of this study was to examine the impact of the Good Behavior Game (GBG) in children with psychiatric disorders, and their teachers, in special education. Teachers were trained by licensed school consultants to implement positive behavior support strategies to elicit desired behavior in students. A total of 389 children and their 58 teachers at 11 schools for special primary education were included in the study. Using a cluster randomized controlled design, special education schools were assigned to an intervention condition or an education as usual condition. An increase in emotional and behavioral problems was found in the control group, whereas no change was seen in the intervention group, indicating a modest intervention effect. No effects were found on children's relationships with teachers or peers. The GBG affected teachers' sense of self-efficacy in engaging students in schoolwork, but no effects were found on teachers' self-efficacy in classroom management or on teachers' burnout symptoms. Thus, although children with psychiatric disorders and their teachers in special education can benefit from the GBG, given the partial effects and modest effect sizes, a longer duration program complemented with additional elements is recommended.